The neotype designation for Podismopsis gynaemorpha Ikonnikov, 1911 (Orthoptera: Acrididae) - Storozhenko, Sergey Yu. (Zootaxa, 2021)
The grasshopper genus Podismopsis Zubowsky, 1900 consists of 39 species distributed in Europe (Switzerland, Austria, Montenegro, and Romania), Russia (European part, Siberia, Far East), Mongolia, China, Korea, and Japan (Zubowsky, 1900; Lu et al., 2011; Storozhenko, 2021; Cigliano et al., 2021). One of them, Podismopsis gynaemorpha Ikonnikov, 1911, was described from Evseevka village (Russia, Primirskii krai) based on two males (Ikonnikov, 1911). Majority of types of the species described by Ikonnikov are deposited in the collection of the Zoological Museum of the Moscow State University (Storozhenko, 1990) while a part of type specimens are stored in the collections of the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. I carefully examined both these collections and found that the syntypes of Podismopsis gynaemorpha are lost. Here the neotype of this species is designated, described and illustrated for stability of nomenclature and according to Article 75 of the Code (ICZN, 1999).